Volatile Composition and Sensory Characterization of Dry White Wines Made with Overripe Grapes by Means of Two Different Techniques - Pau Sancho-Galán; Antonio Amores-Arrocha; Víctor Palacios; Ana Jiménez-Cantizano (Foods, 2022)
Grape over-ripening is a technique that has historically been used for the production of white wines in southern Spain. However, this technique is still widely used for the production of sweet wines. In this study and after recently proving the feasibility of making dry white wines from overripe grapes with and without the presence of grape skin in a warm climate zone, the sensory characterization and analysis of the major and minor volatile compounds in dry white wines made from overripe grapes are presented for the first time. Two over-ripening techniques (sun-drying and climatic chamber drying) were studied for two different periods of time (48 and 96 h), as has the presence of grape skins during alcoholic fermentation. Grape over-ripening implies modifications in the composition of both the major and minor volatile compounds in wines. In terms of sensory analysis, wines with a similar profile were obtained year-on-year. The results of the preference test show that the wines made from grapes that had been over-ripened in the sun for 96 h were preferred by the tasting panel for both vintages. Thus, grape over-ripening under the sun could be considered as a resilience and adaptation technique for increased temperature conditions during the ripening season caused by the effects of climate change.